The Relationship Between Anxiety Level And Delivery Process In Primigravida Women In Kiki Sutresni Labor Clinic - Meria Turnip; Nuri Kayana (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Pregnancy and childbirth is a struggle full of risks for a woman, so this event will add to the emotional intensity and inner stress for every woman. Anxiety often accompanies during pregnancy and will reach its peak during labor. Childbirth becomes an experience that requires hard work and tiring struggle for women. The purpose of this study was to determine the relationship between the level of anxiety and labor in primigravida mothers. This type of research is analytic using a cross-sectional design. The population in this study were all third trimester primigravida mothers who came to give birth at the Kiki Sutresni Maternity Clinic as many as 45 people from February to April 2022. The sample in this study was purposive sampling using the slovin formula with a total sample of 31 people. Data analysis was performed using univariate analysis, bivariate with chi-square test. The results of bivariate analysis using the chi-square test showed that there was a relationship between the level of anxiety and labor in primigravida mothers (p=0.001). It is recommended that health services can provide information related to the delivery process and other factors that can provide good readiness for third trimester mothers so that labor goes well.